Intravenous Administration of Heat Shock-Treated MSCs Can Improve Neuroprotection and Neuroregeneration in Canine Spinal Cord Injury Model - Woo Keyoung Kim; Wan Hee Kim; Oh-Kyeong Kweon; Byung-Jae Kang (Animals, 2020)
Transplantation of mesenchymal stem cells (MSCs) is a promising treatment for spinal cord injury (SCI). However, many transplanted cells die within a few days, eventually limiting the efficacy of cellular therapy. To overcome this problem, we focused on the potential of heat shock (HS) proteins in facilitating recovery from cell damage and protecting against cytotoxicity. PCR results showed that the expression of neurotrophic factor, anti-inflammatory, stemness, and homing genes increased in HS-treated MSCs. We investigated whether HS-treated MSCs could promote recovery of hindlimb function in an acute canine SCI model. We compared the effects of intravenous transplantation with (i) lactated Ringer’s solution as a control, (ii) green fluorescent protein-expressing MSCs (MSCs-GFP), and (iii) GFP-expressing and HS-treated MSCs (MSCs-GFP-HS). Spinal cords were harvested at four weeks and used for Western blot and histopathological analyses. The MSCs-GFP-HS group showed significant improvements in hindlimb function from weeks 3 and 4 compared with the other groups. This group also showed higher expression of neural markers, fewer intervening fibrotic changes, and pronounced myelination. These results suggest that induction of an HS response in MSCs could promote neural sparing. In conclusion, transplantation of HS-treated MSCs could improve neuroprotection and neuroregeneration in acute SCI.